Boris Groys’ Theory of Equal Rights in Aesthetics - Tang, Shijia (International Journal of Culture and History, 2024)
The concept of aesthetic equality was put forward by Groys, one of the important contemporary art theorists and critics, against the background of the decline of multiculturalism and the emergence of the drawbacks of postmodernism. This concept is mainly aimed at the overcorrection of postmodernism, which regards the confrontation with mainstream culture and traditional values as a problem of political correctness. It refers to the equality of aesthetic judgment and aesthetic choice. Aesthetic value judgment can not be evaluated according to the commercial value in the market circulation, nor can it be evaluated only according to the cultural value in the art history, let alone whether it conforms to or resists the mainstream culture, it should be judged according to its directivity to the infinite possibility of the absence of image and art. According to Groys, aesthetic equality is not only an expression of artistic autonomy, but also an expression of artistic power. Different from other theorists’ discussion of artistic autonomy in the framework of self-discipline or heteronomy, he regards it as a force of resistance and liberation, the contemporary phenomenon of political aestheticization and the politicization of aesthetics all show the function of this power.